Characteristics of Esodeviation Related to Hyperopia in Children Aged 4 to 6 Years: A Retrospective Cohort Study - Yoon, Yi Sang; Kim, Ungsoo Samuel (Korean journal of ophthalmology, 2025)
Purpose: To investigate the characteristics of esotropia associated with hyperopia in children aged 4 to 6 years.Methods: Medical charts of 142 patients (60 boys and 82 girls; age range, 4–6 years) with esotropia and hyperopia (≥1.5 diopters after cycloplegic refraction) were retrospectively reviewed. Patients were classified into four groups: (1) fully corrected accommodative esotropia (FCAET); (2) accommodative esotropia (AET) with residual deviation ≤8 prism diopters; (3) partially AET (PAET) with residual deviation ≥10 prism diopters; and (4) nonaccommodative esotropia (NAET). Clinical parameters, including best-corrected visual acuity, angle of esodeviation, and refractive errors, were analyzed to identify predictors of esodeviation type.Results: Female patients were significantly more likely to achieve good control with glasses (p = 0.044). Visual acuity in the better and worse eyes and the prevalence of anisometropic amblyopia did not differ among groups (p = 0.430, p = 0.124, and p = 0.189, respectively). The hyperopia (spherical power) of the AET group was significantly higher than that of the NAET group (p = 0.028), and the spherical equivalent was also more hyperopic in the AET group compared with the NAET group (p = 0.040). Near esodeviation in the FCAET group was significantly smaller than that in the AET group (p = 0.003), whereas esodeviation at distance did not differ among groups (p = 0.115).Conclusions: Larger angles of esodeviation and lower degrees of hyperopia were associated with a reduced likelihood of successful correction with glasses. Multiple factors should therefore be considered when predicting motor outcomes of accommodative esotropia prior to a trial of spectacle correction.